Power distance and employee silence: a review in the superior subordinate’s relationship / Etty Harniza Harun ... [et al.] - Harun, Etty Harniza; Abdul Rahim, Hasni; Mohamad Salleh, Musdiana; Ismail, Junaida (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Hofstede (1992) define culture as the collective programming of the mind that distinguishes the members of one group or category of people from another. The purpose of this review paper is to understand how differences in culture particularly related to power distance may give effect to respond given by employees at workplace. Organizational cultures are the way people realize what goes on in their organizational environment. Meanwhile, the power distance is related to the different solution to the basic problem of human inequality in organization. Therefore, this paper aims to explore a conceptual review on the differences of power distance practised in terms of high and low orientation; and its impact toward the employee silence, as stated in the Hofstede’s Theory Dimensions of Culture.